Rhodotorula Endogenous Endophthalmitis: A Novel Harbinger of the Injection Drug Epidemic in the United States - Preston M. Luong; Basilio Kalpakian; Lawrence J. Jaeger; Timothy Lahey; Christopher B. Chapman; Michael E. Zegans (Case Reports in Infectious Diseases)
Endogenous endophthalmitis is a rare but feared infectious ocular complication of injection drug use (IDU). The recent opioid epidemic in the United States threatens to increase the incidence of this disease. We report the first case of endogenous endophthalmitis in the United States caused by the emerging fungal pathogen Rhodotorula in an injection drug user which led to no light perception vision (NLP). Worldwide experience with Rhodotorula endogenous endophthalmitis is limited, but existing cases suggest infection by this particular fungal genus has a grim prognosis.